Psychometric properties of the hospital birth satisfaction scale: Birth in Brazil survey - Dayana Dourado de Oliveira Costa; Valdinar Sousa Ribeiro; Marizélia Rodrigues Costa Ribeiro; Ana Paula Esteves-Pereira; Lucas Guimarães Cardoso de Sá; Joana Athayde da Silva Cruz; Maria do Carmo Leal; Antônio Augusto Moura da Silva
The objective of this study was to analyze the psychometric properties of the hospital birth satisfaction scale with data from the first follow-up interview of the Birth in Brazil survey. The 11 questions of the scale were asked by telephone up to six months after discharge in a stratified random sample of 16,109 women residing in all five regions of the country. The sample was randomly divided into two halves. Exploratory factor analysis (EFA) was applied to the first half in order to identify the scale's factorial structure. The scree plot suggested the scale to be one-dimensional. The EFA demonstrated a good fit of the one-dimensional model. Factor loadings were greater than 0.5 for all items, except for the mean time transpired between leaving the home and arriving at the maternity hospital, which was excluded from the next analysis. The confirmatory factor analysis applied to the sample's second half with the remaining ten items had a good fit and the factor loadings were > 0.50 with p-values < 0.001. The associations between birth satisfaction and the external variables, the mother's education level (standardized coefficient = 0.073; p = 0.035), private insurance (SC = 0.183; p < 0.001) and having a companion at some point during the hospitalization for labor (SC = 0.193; p = 0.001) were all as expected. There was evidence of configural and metric invariance according to type of hospital (private or public) and type of delivery (cesarean or vaginal). These results showed that the hospital birth satisfaction scale in Brazil is a one-dimensional instrument composed of ten items.